SPECTROSCOPIC PROPERTIES AND ESTIMATION OF GROUND AND EXCITED STATE DIPOLE MOMENTS OF BIOLOGICALLY ACTIVE FLUORESCENT MOLECULE FROM ABSORPTION AND EMISSION SPECTRA: Life Science-Spectroscopy - PATIL, SHIVARAM N.; F.M. SANNINGANNAVAR; B.S NAVATI; N.R. PATIL; R.A. KUSANUR; R.M. MELAVANKI (International Journal of Life Science and Pharma Research, 2014)
The absorption and emission spectra of fluorescent molecule namely 6-Methyl-3-[1-(4, 5-dicarbomethoxy-1, 2, 3-triazoloacetyl)] coumarin (6MDTC) has been recorded at room temperature in solvents of different polarities. The exited state (µe) dipole moment was estimated from Lippert’s, Bakhshiev’s and KawskiChamma-Viallet’s equations using the variation of Stoke’s shift with the solvents of different polarities using dielectric constant and refractive index. The geometry of the molecule was fully optimized and the ground state dipole moment (µg) was also calculated theoretically by Gaussian 03 software using B3LYP/6- 31g* level of theory. The µg and µe were calculated by solvatochromic shift method and µe was also determined in combination with µg. It was observed that µe was greater than that of the µg, indicating a substantial redistribution of the π-electron densities in a more polar excited state for this coumarin. Further, the changes in dipole moment (∆µ) was calculated both from solvatochromic shift method and on the basis of microscopic empirical solvent polarity ( ) and the values are compared.